THE RELATIONSHIP BETWEEN SELF-CONFIDENCE AND ANXIETY OF PUBLIC SPEAKING IN COLLEGE STUDENTS - Ikhsanto, Aldricho Bagus; Nastiti, Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: A student is someone who is studying at a college or university. The ability to speak in public becomes very important for students and or becomes a demand that must be fulfilled in the competitive globalization era. Method: This study used a correlational quantitative approach with a population of 173 students from Mayjen Sungkono University. The research instruments consisted of a self-confidence scale and a public speaking anxiety scale. Results: The results showed that there is a significant negative correlation between self-confidence and public speaking anxiety. Hypothesis test results = 0.001 or said p value is smaller than 0.05) indicates that self-confidence increases, the anxiety of public speaking decreases. And vice versa. Novelty: It can be concluded that self-confidence plays an important role for students of the Law Study Program at Mayjen Sungkono University. Students are expected to be able to build and improve their confidence by actively participating in various activities that support public speaking skills. For students who still feel less confident, it is recommended to continue learning and participate in trainings that can help them develop their communication skills gradually.